Hf-Ta-c ceramic material based on nitrogen-doped phase transition toughening and preparation method thereof
Patent Information
- Application Number
- CN202611029065.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-16
AI Technical Summary
用于解决现有HfTaC超高温碳化物陶瓷韧性不足、外加增韧相与基体界面匹配性差以及氧化铪相变难以原位调控的问题
[0021]First, this invention uses nitrogen doping as the core control method, rather than simply adding a second phase to achieve toughening. Nitrogen element controls the relative proportions of monoclinic hafnium oxide M phase, orthorhombic hafnium oxide O phase, and tetragonal hafnium oxide t phase in in-situ hafnium oxide by adjusting the local lattice, defects, and hafnium oxide phase stability of Hf-Ta-C ceramics. It also causes at least some metastable t phase/O phase to transform into M phase under cooling stress, external load, or crack tip stress. The volume change and shear strain generated by this phase transformation can form local closing stress at the crack tip, and simultaneously induce crack deflection, bifurcation, and interface energy dissipation. This approach is highly consistent with the research and development concept of constructing controllable phase transformation units inside the Hf-Ta-C matrix in the background technology, and can significantly alleviate the technical defects of external toughening phase agglomeration, interface debonding, and structural instability under high temperature conditions.
Smart Images

Figure CN122916682A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ultra-high temperature ceramic materials technology, and further relates to Hf-Ta-CN solid solution ceramic materials and in-situ toughening technology. Specifically, it is an Hf-Ta-C ceramic material and its preparation method based on nitrogen doping-regulated hafnium oxide phase transformation toughening, which can be used in the nose cone tip of hypersonic vehicles. Background Technology
[0002] HfC, TaC, and their solid solution Hf-Ta-C possess high melting points, high hardness, high elastic modulus, and good high-temperature stability, making them important candidate materials for aerospace thermal protection, engine hot-end components, nozzle throat liners, ablation-resistant components, and wear- and erosion-resistant parts. Compared to single HfC or TaC, Hf-Ta-C solid solutions can improve high-temperature strength and ablation resistance through the synergistic effect of Hf and Ta elements in the carbide lattice, thus attracting widespread attention in the field of ultra-high temperature ceramics. However, Hf-Ta-C-type ultra-high temperature carbide materials have strong covalent bonds and low self-diffusion coefficients, making densification during bulk sintering difficult, and their room-temperature fracture toughness is usually insufficient. Under the combined effects of processing, assembly, thermal cycling, and mechanical loading, cracks tend to propagate rapidly along grain boundaries, pores, or local defects, leading to brittle failure. Therefore, how to improve fracture toughness without compromising the high-temperature stability, density, and hardness of Hf-Ta-C is a key issue in the engineering applications of this type of material.
[0003] To improve the brittleness of ultra-high temperature carbides, current mainstream toughening techniques mainly include multi-component solid solution or high-entropy regulation, toughening with metal particles or metal phase second phases, and fiber / whisker bridging and layered structure design. All of these approaches can improve the fracture toughness, crack propagation resistance, or strength-toughness synergy of materials to some extent, but their mechanisms of action, applicable boundaries, and mobility in Hf-Ta-C based ultra-high temperature carbides differ significantly.
[0004] Specifically, multi-component solid solution or high-entropy modulation can improve hardness, strength, and resistance to crack initiation through lattice distortion, valence electron structure adjustment, and improvement of local slip capability. In Toher C, Oses C, Esters M, HicksD, Kotsonis GN, Rost CM, Brenner DW, Maria JP, Curtarolo S. High-entropyceramics: Propelling applications through disorder [J]. MRS Bulletin, 2022,47:194-202., it is proposed that high-entropy ceramics can expand the composition space through multi-component disordered structures and achieve performance control advantages. In Sangiovanni DG, Mellor W, Harrington T, Kaufmann K, Vecchio K. Enhancing plasticity in high-entropy refractory ceramics via tailoring valence electron concentration [J]. Materials & Design, 2021, 209:109932., it is proposed that adjusting the valence electron concentration of high-entropy refractory ceramics can improve their fracture resistance. However, these methods mainly alter the intrinsic bonding and slip tendency of the matrix, lacking the ability to actively release phase transformation volume effects at the already formed crack tips. Furthermore, multi-component designs may lead to problems such as compositional segregation, narrowing of the sintering window, and complex evaluation of the microstructure stability during high-temperature service. Toughening with metal particles or a second metal phase can improve the room-temperature toughness of ceramics by utilizing the plastic deformation of the metal phase, crack bridging, interface debonding, and crack deflection. The fracture toughness of the Al2O3-Al metal-ceramic composite system was reported to be approximately 4.0 MPa·m in Park BG, Crosky AG, Hellier A K. Material characterisation and mechanical properties of Al2O3-Al metal matrix composites [J]. Journal of Materials Science, 2001. 1 / 2However, the melting point and high-temperature mechanical stability of metallic phases are generally lower than those of ultra-high temperature ceramic phases such as HfC, TaC and their solid solutions. They are prone to softening, melting, oxidation or interfacial reactions in ultra-high temperature environments, making it difficult to maintain stable toughening effects over a long period. Fiber / whisker bridging and layered structure design can significantly increase crack propagation paths through pull-out, bridging, layering propagation and interfacial friction. In Mor M, Vinci A, Failla S, Galizia P, Zoli L, Sciti D. A novel approach for manufacturing of layered, ultra-refractory composites using pliable, short fibre-reinforced ceramic sheets [J]. Journal of Advanced Ceramics, 2023, 12(1):155-168., it was proposed that using short fiber-reinforced ceramic sheets to construct layered ultra-high temperature composites can improve damage tolerance; however, such structures usually rely on complex forming and interface design, the material properties are directional, and the long-term stability of the fiber / interface in oxidative ablation environments still needs to be controlled.
[0005] Furthermore, HfO2 itself possesses polymorphic structures such as monoclinic, tetragonal, and orthorhombic phases, providing a potential toughening basis as an in-situ oxidation phase for Hf-based ultra-high temperature carbides. In the paper "The high-toughness mechanism of heterogeneous solid solution HfC-TaC-HfO2 composite ceramics [J]. Composites Communications, 2024, 51:102097," it was proposed that HfC-TaC-HfO2 composite ceramics can achieve toughness improvement through heterogeneous solid solution and the participation of the hafnium oxide phase. This indicates that the introduction of HfO2 into HfC / TaC-like ceramic systems can inhibit crack propagation to a certain extent, and its fracture toughness can be increased to approximately 5 MPa·m. 1 / 2 However, this type of toughening mainly relies on passive energy dissipation mechanisms such as heterostructure, interfacial interaction, or crack deflection. It does not take the stress transformation between the tetragonal, orthorhombic, and monoclinic phases in HfO2 as a designable and controllable phase transformation toughening core. Therefore, its active closure effect on crack tips and the extent of toughening are still limited. Summary of the Invention
[0006] The purpose of this invention is to address the shortcomings of existing technologies by proposing a nitrogen-doped, hafnium oxide phase transformation-toughened Hf-Ta-C ceramic material and its preparation method. This addresses the problems of insufficient toughness in existing HfTaC ultra-high temperature carbide ceramics, poor interface matching between the added toughening phase and the matrix, and difficulty in in-situ control of the hafnium oxide phase transformation. By controlling the Hf-Ta-C matrix lattice, defect structure, oxygen vacancy state, and hafnium oxide phase stability with nitrogen, the in-situ generated nitrogen-containing hafnium oxide undergoes a controllable transformation from a tetragonal / orthorhombic phase to a monoclinic phase under cooling, stress, or service thermo-oxidative environments. Furthermore, the amount and distribution of oxide formation are controlled with the aid of vacuum degree, thereby creating phase transformation volume expansion, residual compressive stress, and crack deflection at the crack tip, thus improving the toughness and mechanical properties of the Hf-Ta-C material.
[0007] To achieve the above objectives, the technical solution of the present invention includes the following:
[0008] A nitrogen-doped hafnium oxide phase transformation toughening Hf-Ta-C ceramic material is disclosed. Using Hf-Ta-CN solid solution ceramic as the matrix, a nitrogen-containing hafnium oxide phase is generated in situ within the matrix. This phase is dispersed at grain boundaries, triple grain boundaries, pore edges, and the area surrounding crack propagation paths. The nitrogen-containing hafnium oxide phase includes tetragonal hafnium oxide, orthorhombic hafnium oxide, and monoclinic hafnium oxide. Some of the tetragonal / orthorhombic hafnium oxide undergoes a martensitic phase transformation under cooling stress, applied load, or crack tip stress, converting into monoclinic hafnium oxide. The in-situ toughening and strengthening of the Hf-Ta-C matrix is achieved by utilizing the volume expansion effect, transformation-induced residual compressive stress effect, and crack deflection effect brought about by the phase transformation.
[0009] Furthermore, the above-mentioned Hf-Ta-CN solid solution ceramic is prepared by mixing HfC, TaC, HfN and TaN powders and then by spark plasma sintering (SPS); wherein the atomic ratio of Hf to Ta is 1:1.
[0010] Furthermore, the aforementioned nitrogen-containing hafnium oxide phase is selected from HfO. 2-x N x The hafnium oxide phase containing nitrogen and oxygen vacancies, the tetragonal phase HfO2, the orthorhombic phase HfO2, the monoclinic phase HfO2, or a combination thereof, allows nitrogen to enter the interstitial sites of the hafnium oxide lattice and replace some oxygen sites, thereby regulating the oxygen vacancy concentration and the lattice distortion state.
[0011] Furthermore, in the above-mentioned Hf-Ta-CN solid solution ceramics, the molar ratio of carbon to nitrogen (C:N) is 9:1, 7:3, or 5:5. By adjusting the C / N molar ratio, the relative contents of tetragonal, orthorhombic, and monoclinic phases in the hafnium oxide phase, as well as the distribution state of the hafnium oxide phase at the grain boundaries, can be controlled.
[0012] Furthermore, the above-mentioned ceramic material exhibits Hf-Ta-C ceramic diffraction peaks in X-ray diffraction tests, and shows m(-111) and m(111) characteristic peaks corresponding to monoclinic HfO2 and t(101) / o(111) characteristic peaks corresponding to tetragonal HfO2 / orthorhombic HfO2 in the range of 28°~33°; with the increase of nitrogen doping ratio, the relative intensity of the t(101) / o(111) characteristic peak and the m phase characteristic peak changes.
[0013] Furthermore, the aforementioned nitrogen-containing hafnium oxide phase appears as a gray dispersed phase in the backscattered image of a scanning electron microscope. Ta and Hf elements are uniformly distributed in the Hf-Ta-C matrix, and oxygen elements are enriched in the gray dispersed phase. The characteristic size of the gray dispersed phase is 0.05 μm to 5 μm.
[0014] Furthermore, the relative density of the aforementioned ceramic material is not less than 97.4%, the elastic modulus is between 568.8±25.93 GPa and 640.9±45.44 GPa, and the fracture toughness is 4.2±0.43 MPa·m. 1 / 2 Up to 6.8±0.29 MPa·m 1 / 2 .
[0015] Meanwhile, a method for preparing Hf-Ta-C ceramic materials based on nitrogen doping-controlled hafnium oxide phase transformation toughening is also proposed, including the following steps:
[0016] (1) Weigh HfC powder, TaC powder, HfN powder and TaN powder according to the target Hf / Ta atomic ratio and C / N molar ratio to obtain composite raw material powder;
[0017] (2) The composite raw material powder is subjected to wet ball milling, drying and sieving to uniformly disperse Hf, Ta, C and N elements to obtain nitrogen-doped Hf-Ta-C precursor powder;
[0018] (3) The nitrogen-doped Hf-Ta-C precursor powder was placed in a graphite mold and subjected to spark plasma sintering (SPS) under a vacuum atmosphere to obtain nitrogen-containing Hf-Ta-C ceramics.
[0019] (4) During the sintering cooling, subsequent heat treatment or controlled oxidation before service, some Hf elements are formed in situ into nitrogen-containing hafnium oxide phase, and some of the tetragonal hafnium oxide / orthorhombic hafnium oxide is transformed into monoclinic hafnium oxide phase to obtain nitrogen-doped induced hafnium oxide phase transformation toughened Hf-Ta-C ceramic material.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] First, this invention uses nitrogen doping as the core control method, rather than simply adding a second phase to achieve toughening. Nitrogen element controls the relative proportions of monoclinic hafnium oxide M phase, orthorhombic hafnium oxide O phase, and tetragonal hafnium oxide t phase in in-situ hafnium oxide by adjusting the local lattice, defects, and hafnium oxide phase stability of Hf-Ta-C ceramics. It also causes at least some metastable t phase / O phase to transform into M phase under cooling stress, external load, or crack tip stress. The volume change and shear strain generated by this phase transformation can form local closing stress at the crack tip, and simultaneously induce crack deflection, bifurcation, and interface energy dissipation. This approach is highly consistent with the research and development concept of constructing controllable phase transformation units inside the Hf-Ta-C matrix in the background technology, and can significantly alleviate the technical defects of external toughening phase agglomeration, interface debonding, and structural instability under high temperature conditions.
[0022] Secondly, this invention innovatively sets the vacuum degree of post-sintering heat treatment as an auxiliary control parameter for the in-situ precipitation behavior of nitrogen-containing oxides. Within the suitable vacuum degree / low oxygen partial pressure range, the oxidation reaction can be precisely controlled. This allows for the directional control of the precipitation content, grain size, and dispersion morphology of nitrogen-containing hafnium oxide at grain boundaries, triple grain boundaries, pore edges, and high-risk crack propagation paths. On the one hand, this ensures that the precipitated oxides can play an effective toughening role as phase transformation units. On the other hand, it prevents the problems of excessive oxide precipitation, grain coarsening, or interconnection leading to new crack sources. This control method, combined with the phase stability modification brought about by nitrogen doping, forms a synergistic effect, which can simultaneously optimize the density, hardness, elastic modulus, fracture toughness, and high-temperature service stability of Hf-Ta-C composite materials, achieving a balanced improvement in multiple key mechanical and heat resistance properties. Attached Figure Description
[0023] Figure 1 The images show X-ray diffraction patterns of samples with different C / N ratios and undoped Hf-Ta-C samples in the embodiments of the present invention, as well as magnified views of characteristic peaks of different phases of hafnium oxide.
[0024] Figure 2 These are scanning electron microscope images of undoped Hf-Ta-C and nitrogen-doped Hf-Ta-C samples with different C / N ratios in the embodiments of the present invention.
[0025] Figure 3 This is a magnified view of the hafnium oxide phase and the energy spectrum distribution of Ta, Hf, and O elements in the undoped Hf-Ta-C sample in this embodiment of the invention. Detailed Implementation
[0026] The present invention will now be further described with reference to the accompanying drawings.
[0027] Example 1: Refer to Appendix Figure 1-3This invention proposes a ceramic material for in-situ toughening of HfTaC through nitrogen-doped hafnium oxide phase transformation. The material uses Hf-Ta-CN solid solution ceramic as a matrix and contains in-situ generated hafnium oxide phases distributed at grain boundaries, tri-junction grain boundaries, pore edges, and near crack propagation paths. These nitrogen-containing hafnium oxide phases include tetragonal HfO2, orthorhombic HfO2, and monoclinic HfO2, with some of the tetragonal / orthorhombic HfO2 transforming into monoclinic HfO2 under cooling stress, applied load, or crack tip stress. The in-situ toughening and strengthening of the Hf-Ta-C matrix is achieved by utilizing the volume expansion effect, phase transformation-induced residual compressive stress effect, and crack deflection effect brought about by the phase transformation.
[0028] In this embodiment, the Hf-Ta-CN solid solution ceramic is prepared by mixing HfC, TaC, HfN, and TaN powders and then performing spark plasma sintering (SPS); wherein the atomic ratio of Hf to Ta is 1:1. The aforementioned nitrogen-containing hafnium oxide phase is selected from HfO. 2-x N x The hafnium oxide phase contains nitrogen and oxygen vacancies, including tetragonal HfO2, orthorhombic HfO2, monoclinic HfO2, or combinations thereof. Nitrogen enters the interstitial sites of the hafnium oxide lattice and replaces some oxygen sites, thereby regulating the oxygen vacancy concentration and lattice distortion state. In the above-mentioned Hf-Ta-CN solid solution ceramics, the molar ratio of carbon to nitrogen (C:N) is 9:1, 7:3, or 5:5. By adjusting the C / N molar ratio, the relative contents of the tetragonal, orthorhombic, and monoclinic phases in the hafnium oxide phase, as well as the distribution state of the hafnium oxide phase at the grain boundaries, can be controlled.
[0029] See attached document Figure 1 In this embodiment, the above-mentioned ceramic materials were tested using X-ray diffraction. HTC represents the undoped Hf-Ta-C sample, and THC9N1, THC7N3, and THC5N5 represent nitrogen-doped Hf-Ta-C samples with C / N molar ratios of 9:1, 7:3, and 5:5, respectively. Figure 1 It can be seen that each sample has Hf-Ta-C ceramic diffraction peaks; and in the range of 28°~33°, the characteristic peaks of m(-111) and m(111) corresponding to monoclinic HfO2 and the characteristic peaks of t(101) / o(111) corresponding to tetragonal HfO2 / orthorhombic HfO2 appear; as the nitrogen doping ratio changes, the relative intensity of the t(101) / o(111) peak and the m phase peak changes, indicating that nitrogen doping can regulate the hafnium oxide phase composition and the degree of transformation from tetragonal / orthorhombic phase to monoclinic phase.
[0030] See attached document Figure 2The aforementioned nitrogen-containing hafnium oxide phase was visualized using a scanning electron microscope. Backscattered images showed a gray dispersed phase and a small amount of porosity in both the undoped Hf-Ta-C sample and the THC9N1, THC7N3, and THC5N5 samples. In this embodiment, the characteristic size of the gray dispersed phase is 0.05 μm to 5 μm. Figure 3 As can be seen from the 2.5 μm magnified view of the hafnium oxide region in the upper right corner of the undoped Hf-Ta-C sample, and the energy dispersive spectral distribution diagrams of Ta, Hf, and O elements, the gray dispersion corresponds to the oxygen-rich hafnium oxide phase. Ta and Hf elements are relatively uniformly distributed in the Hf-Ta-C ceramic, while oxygen is enriched in the local gray area. This result indicates that a dispersed hafnium oxide phase can be formed in situ in Hf-Ta-C ceramic. This hafnium oxide phase can be located near grain boundaries, pore edges, and crack propagation paths, providing a structural basis for phase transformation toughening and crack deflection. In this embodiment, the relative density of the ceramic material is not less than 97.4%, the elastic modulus is 568.8±25.93 GPa to 640.9±45.44 GPa, and the fracture toughness is 4.2±0.43 MPa·m. 1 / 2 Up to 6.8±0.29 MPa·m 1 / 2; When the C / N molar ratio is 9:1, the fracture toughness reaches 6.8 ± 0.29 MPa·m. 1 / 2 .
[0031] Example 2: The method for preparing the ceramic material described in Example 1 provided in this example specifically includes the following steps:
[0032] Step 1. Raw material preparation:
[0033] According to the target Hf / Ta atomic ratio and C / N molar ratio, HfC powder, TaC powder, HfN powder and TaN powder are weighed to obtain composite raw material powder;
[0034] Step 2. Mixing and Activation:
[0035] The composite raw material powder is subjected to wet ball milling, drying, and sieving to uniformly disperse Hf, Ta, C, and N elements, thereby obtaining nitrogen-doped Hf-Ta-C precursor powder. In this embodiment, the composite raw material powder is preferably added to a ball mill jar and wet ball milled using anhydrous ethanol as the ball milling medium. The ball-to-material ratio is set to (5~20):1, the ball milling speed is controlled at 100~600 rpm, and the ball milling time is set to 4~24h. After ball milling, drying and sieving are performed to obtain nitrogen-doped Hf-Ta-C precursor powder with uniform element distribution.
[0036] Step 3. Densification sintering:
[0037] Nitrogen-doped Hf-Ta-C precursor powder was loaded into a graphite mold and subjected to spark plasma sintering (SPS) under vacuum. The preferred sintering temperature was 1800–2200 °C, the heating rate was 50–150 °C / min, the holding time was 5–20 min, and the sintering pressure was 20–60 MPa, resulting in a nitrogen-containing Hf-Ta-C ceramic matrix. This step ensures complete solid solution of HfC, TaC, HfN, and TaN, and allows nitrogen to enter the carbide lattice, grain boundary regions, or defect-rich regions.
[0038] Step 4. In-situ oxidation and phase transition control:
[0039] During sintering and cooling, subsequent low-oxygen partial pressure heat treatment, air heat treatment, or controlled oxidation before service, some Hf elements are situ-formed nitrogen-containing hafnium oxide phases on the matrix surface, grain boundaries, pore edges, or defects. The ratio of tetragonal HfO2, orthorhombic HfO2, and monoclinic HfO2 is adjusted. When the material is subjected to external load or thermal stress, the crack tip induces a transformation of tetragonal HfO2 / orthorhombic HfO2 to monoclinic HfO2. This phase transformation is accompanied by volume expansion and shear deformation, which can form a closing stress at the crack tip and induce crack deflection. Thus, a nitrogen-doped hafnium oxide phase transformation toughened Hf-Ta-C ceramic material is obtained.
[0040] Example 3: The ceramic material proposed in this example is the same as in Example 1, and the overall implementation steps of the preparation method are the same as in Example 2. A set of preferred parameters is given to further illustrate the preparation process of the material of the present invention.
[0041] In this embodiment, HfC powder, TaC powder, HfN powder, and TaN powder are used as raw materials, with an atomic ratio of Hf to Ta of 1:1 and C:N molar ratios of 9:1, 7:3, and 5:5, respectively. The powders are mixed with anhydrous ethanol and then subjected to planetary ball milling, preferably with a ball-to-powder ratio of 10:1, a milling speed of 300 rpm, and a milling time of 12 h. After milling, the slurry is dried at 80 °C for 12 h and sieved to obtain nitrogen-doped Hf-Ta-C precursor powder. Subsequently, the obtained precursor powder is placed in a graphite mold for spark plasma sintering (SPS). The sintering temperature is set to 2000 °C, the heating rate is 100 °C / min, the holding time is 10 min, the axial pressure is 50 MPa, and the sintering atmosphere is vacuum. After sintering, the powder is cooled in the furnace to obtain a dense nitrogen-containing Hf-Ta-C ceramic matrix. During sintering, HfC, TaC, HfN and TaN undergo solid solution, and nitrogen enters the Hf-Ta-C lattice and participates in regulating the formation and phase transformation of the hafnium oxide phase.
[0042] Example 4: This example further illustrates the toughening mechanism of the present invention, as detailed below:
[0043] When the Hf-Ta-C matrix is subjected to external loads or thermal stress, cracks initially initiate at pores, grain boundaries, or local defects. As the crack propagates to the vicinity of the nitrogen-containing hafnium oxide phase, the stress at the crack tip induces a phase transformation from tetragonal HfO2 to monoclinic HfO2. This transformation is accompanied by volume expansion and shear deformation, subsequently creating a closing stress around the crack tip. Simultaneously, the thermal expansion mismatch and interfacial interactions between the transformation zone and the Hf-Ta-C matrix cause crack deflection, bridging, or bifurcation, thereby consuming crack propagation energy. Because the nitrogen-containing hafnium oxide phase is generated in situ, its interfacial bonding with the Hf-Ta-C matrix is relatively good, which is beneficial for the synergistic effect of transformation toughening, crack deflection, and residual compressive stress toughening.
[0044] Example 5: This example presents some specific applications of the ceramic material described in Example 1, including its use in ultra-high temperature structural components, thermal protection components, hot-end components of aerospace engines, nose cones, wing leading edges, nozzle throat liners, wear-resistant and erosion-resistant ceramic components, or coating / bulk composite components. For coating applications, nitrogen-doped Hf-Ta-C sprayable powder can be prepared first, and then deposited on the surface of C / C composite materials, C / SiC composite materials, tungsten-based alloys, or refractory metal substrates using plasma spraying, vacuum plasma spraying, or laser cladding. A nitrogen-containing hafnium oxide phase transformation toughening layer is then formed in situ through controlled oxidation treatment before service.
[0045] The effectiveness of the present invention will be further explained below with reference to performance test experiments.
[0046] 1. Experiment Content:
[0047] Referring to Table 1, the lattice parameters, relative density, and mechanical properties of the HTC, THC9N1, THC7N3, and THC5N5 samples were tested.
[0048] Table 1: Performance data of undoped HfTaC and nitrogen-doped HfTaC samples with different C / N ratios
[0049]
[0050] 2. Analysis of experimental results:
[0051] The test results are as follows: the HTC sample has a lattice constant of 4.5402 Å, a relative density of 97.5%, an elastic modulus of 568.8 ± 25.93 GPa, and a fracture toughness of 4.2 ± 0.43 MPa·m. 1 / 2 The THC9N1 sample has a lattice constant of 4.5313 Å, a relative density of 97.4%, an elastic modulus of 577.5 ± 20.91 GPa, and a fracture toughness of 6.8 ± 0.29 MPa·m. 1 / 2The THC7N3 sample has a lattice constant of 4.5109 Å, a relative density of 97.8%, an elastic modulus of 592.8 ± 27.67 GPa, and a fracture toughness of 5.8 ± 0.38 MPa·m. 1 / 2 The THC5N5 sample has a lattice constant of 4.4610 Å, a relative density of 97.8%, an elastic modulus of 640.9 ± 45.44 GPa, and a fracture toughness of 6.1 ± 0.53 MPa·m. 1 / 2 .
[0052] The lattice constant of the nitrogen-doped samples gradually decreased from 4.5402 Å to 4.4610 Å, indicating that nitrogen enters the Hf-Ta-C lattice and changes the solid solution lattice state. The relative density of all samples was not lower than 97.4%, indicating that nitrogen doping and SPS sintering can maintain high density. Compared with the undoped HTC sample, the fracture toughness of the THC9N1 sample increased from 4.2 ± 0.43 MPa·m. 1 / 2 Increased to 6.8 ± 0.29 MPa·m 1 / 2 The increase was approximately 62%; the elastic modulus of the THC5N5 sample increased to 640.9 ± 45.44 GPa. These results indicate that appropriate nitrogen doping can significantly improve the toughness and mechanical properties of Hf-Ta-C materials by controlling the hafnium oxide phase transition and grain boundary structure while maintaining density.
[0053] The above experimental analysis proves the correctness and effectiveness of the method proposed in this invention.
[0054] The parts of this invention not described in detail are common knowledge to those skilled in the art.
[0055] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Obviously, those skilled in the art, after understanding the content and principle of the present invention, may make various modifications and changes in form and detail without departing from the principle and structure of the present invention. However, these modifications and changes based on the concept of the present invention are still within the scope of protection of the claims of the present invention.
Claims
1. A Hf-Ta-C ceramic material toughened by nitrogen doping-controlled hafnium oxide phase transformation, characterized in that: The ceramic material uses Hf-Ta-CN solid solution ceramic as the matrix, in which a nitrogen-containing hafnium oxide phase is generated in situ. This nitrogen-containing hafnium oxide phase is dispersed in grain boundaries, triple grain boundaries, pore edges, and the area surrounding crack propagation paths. The nitrogen-containing hafnium oxide phase includes tetragonal hafnium oxide, orthorhombic hafnium oxide, and monoclinic hafnium oxide. Some of the tetragonal / orthorhombic hafnium oxide undergoes martensitic transformation under the drive of cooling stress, external load, or crack tip stress, transforming into monoclinic hafnium oxide. The in-situ toughening and strengthening of the Hf-Ta-C matrix is achieved by utilizing the volume expansion effect, phase transformation-induced residual compressive stress effect, and crack deflection effect brought about by the phase transformation.
2. The ceramic material according to claim 1, characterized in that: The Hf-Ta-CN solid solution ceramic is prepared by mixing HfC, TaC, HfN and TaN powders and then performing spark plasma sintering (SPS); wherein the atomic ratio of Hf to Ta is 1:
1.
3. The ceramic material according to claim 2, characterized in that: The nitrogen-containing hafnium oxide phase is selected from HfO. 2-x N x The hafnium oxide phase containing nitrogen and oxygen vacancies, the tetragonal phase HfO2, the orthorhombic phase HfO2, the monoclinic phase HfO2, or a combination thereof, allows nitrogen to enter the interstitial sites of the hafnium oxide lattice and replace some oxygen sites, thereby regulating the oxygen vacancy concentration and the lattice distortion state.
4. The ceramic material according to claim 3, characterized in that: The molar ratio of carbon to nitrogen in the Hf-Ta-CN solid solution ceramic is 9:1, 7:3, or 5:
5. The relative contents of tetragonal, orthorhombic, and monoclinic phases in the hafnium oxide phase, as well as the distribution state of the hafnium oxide phase at the grain boundaries, can be controlled by adjusting the C / N molar ratio.
5. The ceramic material according to claim 1, characterized in that: The ceramic material exhibits Hf-Ta-C ceramic diffraction peaks in X-ray diffraction tests, and shows m(-111) and m(111) characteristic peaks corresponding to monoclinic HfO2 and t(101) / o(111) characteristic peaks corresponding to tetragonal HfO2 / orthorhombic HfO2 in the range of 28°~33°. As the nitrogen doping ratio increases, the relative intensities of the t(101) / o(111) characteristic peak and the m-phase characteristic peak change.
6. The ceramic material according to claim 1, characterized in that: The nitrogen-containing hafnium oxide phase appears as a gray dispersed phase in the backscattered image of a scanning electron microscope. Ta and Hf elements are uniformly distributed in the Hf-Ta-C matrix, and oxygen element is enriched in the gray dispersed phase. The characteristic size of the gray dispersed phase is 0.05 μm to 5 μm.
7. The ceramic material according to claim 1, characterized in that: The ceramic material has a relative density of not less than 97.4%, an elastic modulus of 568.8±25.93 GPa to 640.9±45.44 GPa, and a fracture toughness of 4.2±0.43 MPa·m. 1 / 2 Up to 6.8±0.29 MPa·m 1 / 2 .
8. A method for preparing Hf-Ta-C ceramic materials based on nitrogen doping-controlled hafnium oxide phase transformation toughening, characterized in that, Includes the following steps: (1) Weigh HfC powder, TaC powder, HfN powder and TaN powder according to the target Hf / Ta atomic ratio and C / N molar ratio to obtain composite raw material powder; (2) The composite raw material powder is subjected to wet ball milling, drying and sieving to uniformly disperse Hf, Ta, C and N elements to obtain nitrogen-doped Hf-Ta-C precursor powder; (3) The nitrogen-doped Hf-Ta-C precursor powder was placed in a graphite mold and subjected to spark plasma sintering (SPS) under a vacuum atmosphere to obtain nitrogen-containing Hf-Ta-C ceramics. (4) During the sintering cooling, subsequent heat treatment or controlled oxidation before service, some Hf elements are formed in situ into nitrogen-containing hafnium oxide phase, and some of the tetragonal hafnium oxide / orthorhombic hafnium oxide is transformed into monoclinic hafnium oxide phase to obtain nitrogen-doped induced hafnium oxide phase transformation toughened Hf-Ta-C ceramic material.
9. The method according to claim 8, characterized in that: In step (2), the ball milling medium is anhydrous ethanol, the ball-to-material ratio is 10:1, the ball milling speed is 300 rpm, and the ball milling time is 12 h; in step (3), the discharge plasma sintering temperature is 2000 ℃, the heating rate is 100 ℃ / min, the holding time is 10 min, and the sintering pressure is 40 MPa.
10. An application of the ceramic material according to any one of claims 1 to 7, characterized in that: The ceramic material is used in ultra-high temperature structural components, thermal protection components, hot-end components of aerospace engines, nose cones, wing leading edges, nozzle throat liners, wear-resistant and erosion-resistant ceramic components, or coating / block composite components.